PENERAPAN DIVERSI TERHADAP ANAK YANG MELAKUKAN TINDAK PIDANA - Hulman Panjaitan (Fakultas Hukum Universitas Kristen Indonesia, 2019)
Abstract Diversity implementation by law enforcers is based on the authority of law enforcers called the dis-cretion or discretion of children as the potential of the State in the context of the survival and glory of the nation, is how the governmentâ€™s commitment to make children a top priority in the development of juvenile judges and courts as the last stronghold in the process settlement of children who are fac-ing law in the Court. The police and the community must synergize and develop the same perception of diversion and restorative justice. Parents must participate in providing protection for children by fulï¬lling childrenâ€™s rights, protecting the interests of children and further increasing supervision of the environment and where children play. Keywords: diversity; implementation; children.